Pelindungan Hukum Terhadap Merek Terkenal Jollibee Atas Tindakan Passing Off Merek Terdaftar Tidak Sejenis (Studi Putusan MA Nomor 1051 K/Pdt.Sus-Hki/2023) - Dinda Aprilia Batubara; OK Saidin; Edy Ikhsan (Smart Education, 2025)
A brand as an identifier of the origin of goods or services for producers is a guarantee of the value of production results related to quality and consumer satisfaction. With a brand, a company has built a character for its products which is expected to improve the business reputation for the use of the brand. The research method used in this writing is a combination of normative legal research, with a descriptive analytical research nature. The research approach used is the statute approach and the case approach. Data sources in this study include primary, secondary and tertiary legal materials. The data collection technique used in this study is library research. To analyze all the legal materials that have been collected, this study uses qualitative data analysis. The Defendant's